Case report: Precision guided reactive cancer management: molecular complete response in heavily pretreated metastatic CRC by dual immunotherapy and sorafenib - Aydın, Esranur; Tokat, Ünal Metin; Adibi, Ashkan; Özgü, Eylül; Bilgiç, Şevval Nur; Demiray, Mutlu (Frontiers in Oncology, 2024)
Background: Metastatic colon adenocarcinoma presents significant challenges in treatment, particularly when resistant to standard therapies. Precision oncology, guided by multidisciplinary tumor boards (MTBs), offers a promising way for individualized therapeutic approaches. Integration of comprehensive genomic profiling (CGP) and minimal residual disease (MRD) testing strengthens treatment decision-making, yet challenges persist in identifying and overcoming resistance mechanisms. FLT3 amplification can be one of those resistance/escape mechanisms that needs to be targeted. Case Presentation: This case report presents a 58-year-old male diagnosed with metastatic colon adenocarcinoma with liver metastasis, resistant to conventional treatments. Utilizing CGP and MRD testing, our multidisciplinary MTB identified a complex mutational profile, including APC, DAXX, TP53 mutations, and CDK8 and FLT3 amplifications. With a tumor mutational burden of 10 muts/mb and TPS, CPS scores of 0, immunotherapy was considered, employing dual immune checkpoint inhibitors alongside mebendazole and Lenvatinib targeting the WNT and VEGF/angiogenesis pathways. MRD testing revealed early treatment failure. Re-evaluation identified high copied FLT3 amplification (62 copies) as a resistance mechanism, prompting modification to incorporate sorafenib and dual immunotherapy with mebendazole. Subsequent MRD assessments and radiological scans demonstrated a remarkable therapeutic response, with sustained efficacy and absence of detectable residual disease. Conclusions: This case highlights the successful application of precision oncology principles, facilitated by dynamic MTB-guided treatment strategies. Integration of MRD testing provided early detection of treatment inefficacy, allowing for timely intervention and adaptation of the treatment plan.Additionally, the case highlights the educational value of rare molecular alterations, emphasizing continual learning and refinement of treatment approaches in precision oncology.